STRENGTHENING OF CONCRETE BEAMS WITH PRESTRESSED FRP REINFORCEMENTS - Suhaib Sabah Abdulhameed (Journal of Engineering and Sustainable Development, 2019)
Strengthening of reinforced concrete beams with prestressed Fiber Reinforced Polymer (FRP) sheets showed to be efficient in enhancing the serviceability of the strengthened concrete beams. Yu et al.develop a mechanical prestressing device to prestress FRP sheets to strengthen reinforced concrete members. Yu et al. s experimental results showed that this device overcome the shortcomings associated by using the previously developed prestressing devices. In this research program Yu et al.'s mechanical device was modified to increase the efficiency of it by using light weight material to reduce the additional weight on the strengthened beams caused by the prestressing device in addition, the end anchorage plates were installed vertically rather than horizontally to extend the prestressed FRP sheets to the end regions of the member where high shear stress occurred. This modification in the end anchorage regions is efficient to reduce the possibility of the premature debonding failure. A numerical analysis by using ANSYS (R14.5) computer program was used to simulate the prestressing device. Numerical results showed that using aluminum material is efficient to produce a prestressing mechanical device. The maximum stresses and deflection that generated in the pretressing device upon prestressing Carbon Fiber Reinforced Polymer (CFRP) .......